DEVELOPPEMENT DURABLE ET SAVOIRS AUTOCHTONES : UNE NOUVELLE PERSPECTIVE POUR LES SCIENCES SOCIALES - Coulibaly Djakalidja (European Scientific Journal, ESJ, 2012)
Local knowledge represents for Anthropology a main challenge as this field that was not primarily the concern of social and biological sciences is nowadays the object at once of economic, social, political and environmental stakes. The recognition of this local knowledge as being an integral part into the process of sustainable development in the world brings about a craze of the different actors. The strategies of the actors depend on the interests at stake. As a consequence, NGOs in charge of protecting the environment put forward a discourse on nature to native people in order to serve their cause. It is therefore the duty of social sciences to bring into the open this ambiguity so that local knowledge is defined from a scientific point of view. It is now time to leave the political or economic field to give to local knowledge its scientific basis and essence as well.